2001
DOI: 10.1152/jn.2001.85.5.2166
|View full text |Cite
|
Sign up to set email alerts
|

Post-Episode Depression of GABAergic Transmission in Spinal Neurons of the Chick Embryo

Abstract: Whole cell recordings were obtained from ventral horn neurons in spontaneously active spinal cords isolated from the chick embryo [embryonic days 10 to 11 (E10-E11)] to examine the post-episode depression of GABAergic transmission. Spontaneous activity occurred as recurrent, rhythmic episodes approximately 60 s in duration with 10- to 15-min quiescent inter-episode intervals. Current-clamp recording revealed that episodes were followed by a transient hyperpolarization (7 +/- 1.2 mV, mean +/- SE), which dissipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 47 publications
12
94
0
Order By: Relevance
“…The decrease in GDP frequency was not studied further, but it may well reflect an increase in the time needed to restore neuronal Cl Ϫ gradients after the enhanced dissipation (and a consequent reduction in the driving force for excitatory GABA responses) that is likely to take place during the NO-711-mediated increase in GDP amplitude and duration (cf. Chub and O'Donovan, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in GDP frequency was not studied further, but it may well reflect an increase in the time needed to restore neuronal Cl Ϫ gradients after the enhanced dissipation (and a consequent reduction in the driving force for excitatory GABA responses) that is likely to take place during the NO-711-mediated increase in GDP amplitude and duration (cf. Chub and O'Donovan, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that several mechanisms are recruited to recover and maintain activity levels and that the different mechanisms may have different time courses (13). After glutamatergic blockade, activity recovers in part because of a fast loading of intracellular chloride, which strengthens the unblocked GABAergic currents (22,44). After GABAergic block, there may be fast changes in the probability of release (45) and changes in cellular excitability (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using TTX have demonstrated that the majority of sPSCs recorded are action potentialindependent mPSCs (7,44). Therefore, experiments were performed without TTX (except where mentioned) and are referred to as mPSCs.…”
Section: Pharmacologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…During development, the classical inhibitory neurotransmitters GABA and glycine can be functionally excitatory because the chloride equilibrium potential is above rest as a result of an elevated intracellular chloride concentration (Chub and O'Donovan, 2001) (for review, see Ben Ari, 2002). This leads to a predominance of excitatory synapses that renders developing networks hyperexcitable.…”
Section: Introductionmentioning
confidence: 99%